Dental health of 5-year-olds following community-based oral health promotion in Glasgow, UK - Y. BLAIR, L. MACPHERSON, D. MCCALL & A. MCMAHON (Paediatric Dentistry, 2006)
This paper describes the evaluation of dental health outcomes following a community-based programme of oral health promotion in Glasgow, UK, and discusses the programme’s relevance to improving infants’ oral health in extremely deprived urban communities.